The effect of selenium and vitamin E supplementation on anti-Mullerian hormone and antral follicle count in infertile women with occult premature ovarian insufficiency: A randomized controlled clinical trial - Farhadi Dizaji Safiyeh; Mirghafourvand Mojgan; Shahabi Parviz; Mohammad Alizadeh Sakineh; Sadeghzadeh Oskouei Behnaz (Elsevier, 2021)
Objective: Increased accumulation of reactive oxygen species (ROS) in the process of oogenesis is one of the most well known causes of ovarian insufficiency and decreased ovarian reserve. Selenium and vitamin E as cofactors of glutathione peroxidase plays an important role in the removal of ROS in the ovary. We evaluated the effects of selenium and vitamin E supplementation on anti-Mullerian hormone (AMH) index and antral follicle count (AFC) (primary outcomes) and mean ovarian volume (MOV) and side effects of these supplements (secondary outcome) in infertile women with occult premature ovarian insufficiency (OPOI). Methods: 70 patients were allocated into the control and treatment groups through block randomization method. 35 women in the treatment group received 200 ng selenium and 400IU vitamin E and 35 women in the control group received placebo for a total of 90 days. AMH index, AFC and mean ovarian volume (MOV) were investigated in both groups after 12 months of study. Result: There was no significant difference between groups before intervention in AMH (Mean difference: −0.08; 95% CI: −0.20 to.08; p=0.33), AFC (−0.71; 95%CI: −1.44 to −0.01; p=0.05) and MOV (−0.55; 95% CI: −0.85 to −0.24; p=0.001). There was a significant increase in AMH (mean difference: 0.59; 95% CI: 0.48 to 0.71; p<0.001), AFC (5.08; 95% CI: 4.36 to 5.08; p<0.001) and MOV (2.17; 95% CI: 1.87 to 2.47; p<0.001) in selenium + vitamin E group compared to placebo group 12 months after intervention. These supplements had no side effects. Conclusion: Supplementation with selenium and vitamin E can increase AMH, AFC and MOV in women with OPOI.